(untitled) (Research, Society and Development, 2020)
With the expressive increase in grain productivity in Brazil, mainly soybeans, storage demand has been growing year after year, causing static capacity deficit. In this sense, this study aims to analyze the economic viability of the grain storage system on the rural property through silo bag, comparing delivery and marketing in cereal producers of northwest region of Rio Grande do Sul. Aspects related to producer profitability, storage costs and the technology economic viability were analyzed, considering difference between available market prices and prices based on sales for immediate delivery or after a short storage period. For this, we carried out an exploratory descriptive research, and the variables for feasibility analysis were net present value, internal rate of return, minimum acceptable rate of return, profitability index and payback. Four analyzes were carried out with interest charged for different agricultural investment modalities by financial institutions of Palmeira das Missões, two with interest of 4.8% per year and two with interest of 6.8% per year. With ten years for payment and annual installment, varying the production area in order to analyze the economic viability and the payment capacity based on different reality for each property. The use of silo bag for grain storage on the property is feasible and increases profitability at the time of commercialization. However, it has a limitation in relation of the size area, making it economically feasible from 100 and 130 ha-1.